Pengaruh Kompetensi dan Etos Kerja Guru PAK Terhadap Hasil Belajar Siswa di SMA Negeri 9 Manado - Momongan, Christy Monica (LPPM-Institut Agama kristen Negeri Tarutung, 2024)
One of the national goals is to educate the nation's children. To achieve these national goals, it takes an educator or teacher who has high competence and work ethic. Christian Religious Education teachers who have high competence and work ethic will display quality figures and demonstrate the level of professionalism of teachers who are able to contribute to improving learning outcomes and changing student behavior for the better. This research aimed to analyze the influence of competence and work ethic of Christian Religion education Teachers to students learning achievement at State Senior High School 9 Manado. The method used in this research was a descriptive survey method with quantitative approach. The total population was 575 students. Determination of collecting sample used random sampling and with a total of sampling 85 students. The procedure of collecting data used questionnaires and documentation. The data analysis method used regression multiple linear. The results of multiple analysis found the regression equation Y = 88.202 + 0.038X1 + 0.051X2. Based on that regression equation, it was known that the value of constant 88,202, it mean that if there were no competence and work ethic of Christian Religion education Teachers so the students learning achievement was 88,202. Whereas coefficient value 0,038 meant if the competence increased, so each increasing addition or decreasing addition would influence the students learning achievement 0,038, and the coefficient value 0.051 meant if work ethic of Christian Religion education teachers increased or decreased, so each increasing additional or decreased additional would influence the students learning achievement 0,051. Simultaneously the competence and work ethic of Christian Religious Education teachers influenced to students learning 82%. The conclusion of this research was partially and simultaneously the competence and work ethic of Christian Religious Education teachers influenced to the students learning achievement at State Senior High School 9 Manado.